FAKTOR YANG MEMPENGARUHI MINAT NASABAH BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) KOTABUMI KANTOR CABANG BANDAR LAMPUNG - Kuswarak -; Yuliana Yamin (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2018)
Many factors influence people in taking a decision to connect with a bank. It is certainly basedon someone’s interest. The purpose of this study is to determine the factors that play a role ininfluencing customer interest to the company. The hypothesis of this research is service factor, product,facility and location access affect customers’ interest in BPRS Kotabumi, Branch Office BandarLampung.The result of the research indicate that service factor, product, facility and location access havepositive and significant influence to customers’ interest of BPRS Kotabumi, Branch office BandarLampung and all four factors together influence to customers’ interest of BPRS Kotabumi, Branch officeBandar Lampung. These four factors also affect customers’ interest by 75.9%.